Analyses of the thermal characteristics of construction details at the biogas station plant - P. Junga; P. Trávníček (Research in Agricultural Engineering, 2014)
This paper presents analyses of the thermal characteristics of construction details at the biogas station plant, in order to investigate the impact of the thermal bridges on the energy consumption. Thermal bridges in the building's envelope remain a weak spot in the constructions. Heat losses of biogas plant constructions are a negative phenomenon and cause wasting of energy. If we eliminate thermal bridges in constructions we can achieve a reduction of general heat losses and save a certain amount of heat energy for utilization. Correct structural design of construction details has impact on general environmental and economic characteristics of biogas plant.